Comprehensive analysis of SARS‐CoV‐2 receptor proteins in human respiratory tissues identifies alveolar macrophages as potential virus entry site. Issue 6 (21st February 2023) - Bräutigam, Konstantin; Reinhard, Stefan; Wartenberg, Martin; Forster, Stefan; Greif, Karen; Granai, Massimo; Bösmüller, Hans; Klingel, Karin; Schürch, Christian M
Abstract : Aims: COVID‐19 has had enormous consequences on global health‐care and has resulted in millions of fatalities. The exact mechanism and site of SARS‐CoV‐2 entry into the body remains insufficiently understood. Recently, novel virus receptors were identified, and alveolar macrophages were suggested as a potential viral entry cell type and vector for intra‐alveolar virus transmission. Here, we investigated the protein expression of 10 well‐known and novel virus entry molecules along potential entry sites in humans using immunohistochemistry. Methods and results: Samples of different anatomical sites from up to 93 patients were incorporated into tissue microarrays. Protein expression of ACE2, TMPRSS2, furin, CD147, C‐type lectin receptors (CD169, CD209, CD299), neuropilin‐1, ASGR1 and KREMEN1 were analysed. In lung tissues, at least one of the three receptors ACE2, ASGR1 or KREMEN1 was expressed in the majority of cases. Moreover, all the investigated molecules were found to be expressed in alveolar macrophages, and co‐localisation with SARS‐CoV‐2 N‐protein was demonstrated using dual immunohistochemistry in lung tissue from a COVID‐19 autopsy. While CD169 and CD209 showed consistent protein expression in sinonasal, conjunctival and bronchiolar tissues, neuropilin‐1 and ASGR1 were mostly absent, suggesting a minor relevance of these two molecules at these specific sites. Conclusion: Our results extend recent discoveries indicating a role for these molecules in virus entry at different anatomical sites. Moreover, they support the notion of alveolar macrophages being a potential entry cell for SARS‐CoV‐2. Abstract : Human alveolar macrophages show consistent expression of SARS‐CoV‐2 entry receptor proteins. In the upper respiratory tract, specifically sinonasal and conjunctival epithelium, CD169 and KREMEN1 are reproducibly detectable.